Training and Development and its Impact on Employees Performance and Productivity "A case Study of district Anantnag Private Sector companies located in the District Anantnag Jammu and Kashmir - Bhat, Ajaz Ahmad (Archives of Business Research, 2019)
This study is all about the training and development and to understand the affect of its need or necessity on the internal or external management of the organization, this is the only way to design or give framework of the new innovations or creativity and to implementing the new look over the management of the company we all know organization wants maximum out of the minimum efforts but it needs a proper mentoring of the management and for the same purpose the organization has to adopt the new trends of training sessions and development in the company for making performance better and better in the upcoming future competition for the research study we have to study about the factor of success for the organization and fulfilling the same objective of the research study we have selected 250 sample size for accessing their information about the training and development programs in their work place.